2022
DOI: 10.1021/acs.est.1c07301
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Influence of Wildfire Emissions in the Western United States and Characteristics of Aged Biomass Burning Organic Aerosols under Clean Air Conditions

Abstract: Wildfire-influenced air masses under regional background conditions were characterized at the Mt. Bachelor Observatory (∼2800 m a.s.l.) in summer 2019 to provide a better understanding of the aging of biomass burning organic aerosols (BBOAs) and their impacts on the remote troposphere in the western United States. Submicron aerosol (PM 1 ) concentrations were low (average ± 1σ = 2.2 ± 1.9 μg sm −3 ), but oxidized BBOAs (average O/C = 0.84) were constantly detected throughout the study. The BBOA correlated well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 97 publications
4
28
0
Order By: Relevance
“…Nucleation events at Storm Peak, a mountaintop observatory in the Western USA, in spring are most likely associated with sulfuric acid, whereby NPF events in summer are driven by lowvolatility organics (Yu and Hallar, 2014). Farley et al, 2022 found Siberian BB to be associated with low volatility oxidized organic aerosol, greater O:C elemental ratio, and greater secondary 500 sulfate mass, the later consistent with observations by Sihto et al, 2006 andSchill et al, 2020. BB smoke transported long-range distances thus likely mixes with other aerosol sources, such as sulfate from marine or other sources, leading to an enhancement in small particles.…”
Section: Aerosol Size Distribution and Compositionsupporting
confidence: 77%
See 4 more Smart Citations
“…Nucleation events at Storm Peak, a mountaintop observatory in the Western USA, in spring are most likely associated with sulfuric acid, whereby NPF events in summer are driven by lowvolatility organics (Yu and Hallar, 2014). Farley et al, 2022 found Siberian BB to be associated with low volatility oxidized organic aerosol, greater O:C elemental ratio, and greater secondary 500 sulfate mass, the later consistent with observations by Sihto et al, 2006 andSchill et al, 2020. BB smoke transported long-range distances thus likely mixes with other aerosol sources, such as sulfate from marine or other sources, leading to an enhancement in small particles.…”
Section: Aerosol Size Distribution and Compositionsupporting
confidence: 77%
“…• The higher lower SAE, and higher MSE of Siberian BB events reflected contributions from large particles, for which we propose two hypotheses: o Enhanced secondary processing during long-range transport leading to particle growth, which is supported by SP-AMS measurements of enhanced low-volatility 530 organics and sulfate in Siberian BB reported by Farley et al, 2022. o Fine dust transported alongside smoke, which is supported by CALIPSO and Dust Score satellite products of dust mixed with smoke originating from Siberian Boreal Forest fires.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations